Serum Levels of Sodium Valproate in Patients Suffering from Bipolar Disorders: Comparing Acute and Maintenance Phases of Mania - Kamalinia, G.; Brand, S.; Ghaeli, P.; Abedi, N.; Bajoghli, H.; Sharifi, V.; Zahiroddin, A.; Amini, M.; Rouini, M. R.; Holsboer-Trachsler, E.; Mohammadpoor, A. H. (Pharmacopsychiatry, 2013)
Bipolar disorders (BD) are characterized by episodes of mania and depression. There is evidence that states of psychiatric disorders impact on neurotransmitters, endocrine system and membrane transport and, therefore, it is possible that specific phases of BD differentially influence the pharmacokinetics of some drugs. The aim of the present study was to investigate the drug-disease interaction between sodium valproate, one of the major drugs used in the treatment of bipolar disorder, and acute versus maintenance states of manic episodes.37 patients (mean age±SD=37.54±11.27 years; 23 males, 14 females) suffering from bipolar disorder completed the study. Blood samples were taken during both acute and maintenance states.Neither the trough concentration (p=0.567) nor the internal clearances (p=0.729) of sodium valproate in the acute phase of mania differed statistically or descriptively from those in the maintenance phase. Marginally significant phase by gender interactions were observed.No significant effect of the acute phase of mania was observed in bipolar patients and no relationship could be found between drug pharmacokinetics and disease phase. This may be explained by specific pharmacokinetic features of the drug such as low extraction ratio values. However, phase by gender interactions indicate possible gender-related issues.
Keywords: sodium valproate; bipolar disorder; drug-disease interaction; pharmacokinetics